„Es nimmt sich gut aus“: Mendelssohns Arrangements für Klavier zu vier und zwei Händen - Hoshino, Hiromi (Die Musikforschung, 2022)
This article comprehensively examines Felix Mendelssohn Bartholdy’s piano arrangements for two and four hands, with particular focus on their role in the contemporary dissemination of large scale works at his time and their significance as primary sources in the study of Mendelssohn’s compositional process. From his early childhood, Mendelssohn gave improvised performances on the piano of works not written for this instrument, and he also enjoyed playing four-hand duets with his sister Fanny and close friends. In his own works, he concentrated mainly on four-hand arrangements of his overtures, symphonies, and chamber music for strings, making them as artful and playable as possible. On the other hand, he considered two-hand arrangements as too challenging for amateur musicians (or too simplistic to do justice to the piece), and only published a couple of pieces later in his life. The article also considers the two and four-hand piano arrangements of Mendelssohn’s works by his contemporaries (Carl Czerny, Friedrich Mockwitz, Franz Louis Schubert, Ernst Friedrich Richter, etc.), and sheds light on how he looked through them and occasionally suggested changes. (Vorlage)